P581 Transmural remission improves clinical outcomes up to 5 years in patients with Crohn's Disease. (21st January 2022) - Pedro, J; Botto, I; Fernandes, S; Lemos, J; Neves, J; Campelo, P; Carvalho, D; Bernardo, S; Gonçalves, A R; Valente, A; Moura Santos, P; Rosa, I; et al.
Abstract: Background: Endoscopic remission (ER) is currently endorsed as one of the main treatment targets in Crohn's Disease (CD). In a previous study, we have shown that transmural remission (TR) is associated with better clinical outcomes up to 1-year. It is unknown if these results still hold over a longer follow-up Methods: This was a multicenter study, including 333 CD patients with magnetic resonance enterography (MRE) and colonoscopy evaluation performed within a 6-month interval and at least 5-years of follow-up. Patients were classified as having TR (inactive MRE and colonoscopy), ER (active MRE and inactive colonoscopy), and no remission (NR) (active colonoscopy). The need for surgery, hospitalization, steroids, and biologics was evaluated at 5-years of follow-up. Results: Patients with TR presented lower rates of surgery (1.9% vs 17.9% vs 23.7%, P<0.001 and P=0.008), hospitalization (13.2% vs 30.4% vs 37.9%, P=0.001 and P=0.038), steroids (11.3% vs 21.4% vs 33.0%, P=0.001 and P=0.2), biologics (18.9% vs 51.8% vs 66.5%, P<0.001 and P=0.001), and any adverse outcome (26.4% vs 64.3% vs 78.6%, P<0.001) compared to ER and NR. Comparisons between ER and NR were mostly non-significant in respect to surgery (P=0.474), hospitalization (P=0.352), steroids (P=0.106), biologics (P=0.045), and any adverse outcome (P=0.036). The time until reaching any individual outcome was also significantly longer for TR. In multivariate analysis, endoscopic remission (OR 0.234 95%CI 0.135–0.405, P<0.001) and MRE remission (OR 0.316 95%CI 0.187–0.536, P<0.001) were independently associated with a lower likelihood of reaching any adverse outcome. Conclusion: TR was associated with improved clinical outcomes over 5-years of follow-up. Going beyond ER appears to provide significant clinical benefits in the short and long-term.